1995
DOI: 10.1093/carcin/16.8.1927
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Helicobacter mustelase infection on ferret gastric epithelial cell proliferation

Abstract: The effect of Helicobacter mustelae infection on gastric epithelial proliferation was studied in ferrets colonized with H.mustelae and specific pathogen-free (SPF) ferrets not infected with H.mustelae. Thirteen H. mustelae-infected ferrets between the ages of 13 and 32 months and 16 SPF ferrets between 6 and 18 months were analyzed. Bacterial cultures, urease tests and Warthin-Starry stains were used to identify H.mustelae. Tissues obtained from the antrum and the body regions of the stomach were assayed by pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
27
0

Year Published

1999
1999
2022
2022

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(27 citation statements)
references
References 0 publications
0
27
0
Order By: Relevance
“…H. mustelae is a gastric pathogen that has many biochemical, molecular and phenotypic characteristics similar to those of H. pylori (24). H. mustelae infection was found to increase gastric epithelial proliferation, as noted in H. pylori-infected humans, presumably due to a chronic inflammatory response (25). A previous study suggested that the high tumor incidence reported in mNNG-treated ferrets reflected the involvement of H. mustelae infection in the carcinogenic process in these animals (26).…”
Section: Discussionmentioning
confidence: 81%
“…H. mustelae is a gastric pathogen that has many biochemical, molecular and phenotypic characteristics similar to those of H. pylori (24). H. mustelae infection was found to increase gastric epithelial proliferation, as noted in H. pylori-infected humans, presumably due to a chronic inflammatory response (25). A previous study suggested that the high tumor incidence reported in mNNG-treated ferrets reflected the involvement of H. mustelae infection in the carcinogenic process in these animals (26).…”
Section: Discussionmentioning
confidence: 81%
“…Free radical mediated oxidative DNA damage was involved in this process [21][22][23] . The DNA damage provoked by oxygen free radicals can have very harmful consequences, leading to gene modifications that are potentially mutagenic and/or carcinogenic.…”
Section: Discussionmentioning
confidence: 99%
“…Recent investigations implicated mitogen-activated protein kinases (MAPK) as additional mediators of H pylori-dependent NFκB activation and IL-8 expression. Studies have demonstrated the presence of cross-talk between the MAPK and NFκB pathways [21][22][23][24][25][26][27][28][29][30][31][32][33][34] . MAPK cascades are signal transduction networks that target transcription factors and thus participate in a diverse array of cellular functions including cytokine production.…”
Section: Discussionmentioning
confidence: 99%
“…EGFr, epidermal growth factor receptor; TNFr, tumour necrosis factor receptor; CD95L, CD95 /Apo1/Fas ligand; PTyr, phosphotyrosine activity; MAPKK, mitogen-activated protein kinase kinase; MAPK, mitogen-activated protein kinase; JNK, c-jun amino-terminal kinase; IkK, IkB kinase; IkB, inhibitor KB; NF-kB, nuclear factor kB; COX-2, cyclooxygenase-2. epithelial cell mitogenesis, the increased proliferative activity in gastric mucosa from Helicobacter-infected animals (Yu et al, 1995;Fox et al, 1996;Wang et al, 1998) or patients (Jones et al, 1997;Peek et al, 1997) might be driven by a sustained overexpression of EGF-related growth factors. Also, EGF-related peptides upregulate the expression of COX-2 in cultured gastric mucosal cells (Romano et al, 1998a), and this may stimulate epithelial cell proliferation and inhibit H. pylori-dependent apoptosis (Fig.…”
Section: Host Response To H Pylori-induced Cell Damagementioning
confidence: 99%
“…In super®cial gastritis, gastric mucosa responds to Helicobacter-induced injury by increasing the mitogenic activity of the epithelial cell compartment in the face of the absence of a corresponding increase in apoptosis (Yu et al, 1995;Fox et al, 1996;Jones et al, 1997;Peek et al, 1997;Wang et al, 1998). This might be caused by upregulation of growth factors and COX-2 (Romano et al, 1998a,b;Fu et al, 1999;Zarrilli et al, 1999), which may therefore be regarded as an early event in gastric carcinogenesis associated with H. pylori infection (see also Figs 1 and 2).…”
Section: H Pylori and Gastric Cancermentioning
confidence: 99%